Using Anther Culture Method for Flax Breeding Intensification (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Flax breeding is a long and complicated process based on hybridization and following selection of the best plants. Because of possible occasional cross-pollination the development of genetically stable homozygous lines could last more than 15 years. For more rapid creating of initial material for flax breeding anther culture methods for producing doubled haploid (DH) lines could be used successfully. The goal of this study was to develop the best anther culture protocol for producing DH lines from hybrids included in Latvian flax breeding programme and to do preliminary field evaluation of obtained DH lines. F4 hybrids were used in the experiment. Method, most applicable for establishing of DH from anther cultures, was elaborated; 13 DH lines were obtained during the experiment. Such agronomic important traits, as vegetation period, total plant height, number of seed vessels, number of seeds in a seed vessel, 1000 seeds weight, oil and bast fibre content were evaluated for obtained DH lines. Several accessions showed high 1000 seeds weight, number of seeds in a seed vessel, good oil and bast fibre content. It was concluded that anther culture method is of value of using as an adjunct to classical methods of flax breeding.